Impact of COVID-19 pandemic and lockdown on emergency room access in Northern and Central Italy (Emergency Care Journal, 2021)
In Northern Italy the coronavirus infection has spread since February 2020: the increase in admissions of COVID-19 patients corresponded to a drastic decrease in admissions of regular patients to the Emergency Room (ER). This retrospective study was conducted by Academy of Emergency Medicine and Care (AcEMC). During the lockdown period the accesses were reduced by more than 50%, and in the following months of May and June 2020, there was a recovery clearly below (70%) previous year’s numbers. We have observed a drastic reduction in white and green codes, a fair reduction in yellow codes, while red codes remained stable. The decrease in access to the ER mainly concerned patients with low priority color codes, but also the reduction in the number of accesses of yellow and red codes, insignificant at a superficial glance, is notable. If we consider that yellow and red codes during the months of the lockdown included many patients with COVIDrelated respiratory insufficiency, it is evident that there was a clear reduction in the number of serious illnesses not COVID-related. This is certainly another serious consequence of the COVID-19 pandemic.
Keywords: Overcrowding; COVID-19; triage; emergency room; Italian epidemic